A Study of Potential Drug-Drug Interactions in Indoor Patients of Medicine Department at a Tertiary Care Hospital - Jigar Kapadia, Dhaval Thakor, Chetna Desai and R. K. Dikshit (Journal of Applied Pharmaceutical Science, 2013)
Drug interactions are an important cause of medication errors. The present study was conducted to evaluate the nature and clinical significance of potential drug-drug interactions (DDIs) in inpatients of Medicine Department at a tertiary care hospital in India. The second day prescription of every alternate indoor patient from five randomly selected medical units of a tertiary care hospital were collected. Prescriptions were analyzed for potential DDIs using the web based interaction checkers of Medscape and Current Index of Medical Specialties. The average numbers of drugs per prescription and potential DDIs per prescription and the types, age wise distribution and clinical significance of the potential DDIs were evaluated. A total of 3405 potential DDIs were detected in 257 prescriptions. An average 8.28 drugs were prescribed per prescription. The most common drug groups involved in potential DDIs were diuretics (n=255), NSAIDs (n=225), β blockers (n=143), cardiac glycosides (n=129) and statins (n=122). Potential DDIs were most frequent in patients between 61-75 years of age. The clinical significance was graded as serious (n=123), significant (n=949), minor (n=2328) and contraindicated (n=5). An increased risk of rhabdomyolysis (n=41) and an increase in QTc interval (n=38) were the most common potentially serious DDIs detected. Of the 1077 DDIs (excluding minor DDIs), 615 were pharmacodynamic and 462 were pharmacokinetic interactions. Potential DDIs increased with an increase in the number of prescribed drugs. Improved awareness among prescribers is required to reduce the risks associated with DDIs. Use of drug groups, commonly involved in potential DDIs, should be minimized and optimized while prescribing.
Keywords: Potential drug interactions, Medicine department, Medscape, Current Index of Medical Specialties, Pharmacodynamic interactions, Pharmacokinetic interactions.